Research progress of environment-responsive hydrogel applications in agriculture - Wenxu Zhang; Xuyang Mu; Yan Xu; Guofu Ma; Ziqiang Lei (eXPRESS Polymer Letters)
Environment-responsive hydrogels are environmentally friendly polymeric materials that rapidly respond to their environment by changing their volume or strength when the external environment, such as temperature, pH, light, and magnetism, changes. As environment-responsive hydrogels, they are uniquely flexible and sensitive, enabling them to be used in various applications, and are now at the forefront of polymer science research. Scholars have reviewed more environmentresponsive hydrogels in biomedicine, detection sensors, and drug release. We present a detailed description of the reaction mechanism and preparation process of environment-responsive hydrogels, taking temperature-responsive, pH-responsive, and light-responsive hydrogels as examples. Finally, a summary is given at the end: 1) the application of environmentally responsive hydrogels in agriculture, and 2) the problems and future trends of their application in agriculture.